Isolation and Characterization of Bacteria Associated with Native Entomopathogenic Nematode, Steinernema sp. (Nematoda: Steinernematidae) (Indian Journal of Nematology, 2024)
Isolation and characterization of the bacterial community associated with the infective juveniles (IJs) of entomopathogenic nematode (EPN), Steinernema sp. (AAU St-1) was carried out through microbiological, biochemical, and molecular methods. Based on distinct phenotypic features, six different bacterial isolates were isolated from the IJs of EPN. The bacterial isolates were subjected to 16s RNA analysis and identified as Pseudomonas otitidis, Alcaligenes faecalis (Strain A), Providencia vermicola, Lysinibacillus sp., Xenorhabdus nematophila, and Alcaligenes faecalis (Strain B). The present findings revealed the association of more than one species of bacterial community with Steinernema sp. (AAU St-1).